TAXONOMIC AND ECOLOGICAL STUDY OF WILD BETTA SPECIES FROM BANGKA ISLAND, INDONESIA: DIVERSITY, DISTRIBUTION, AND HABITAT CHARACTERISTICS - Subriyono, Subriyono; Asbio, Geby; Sumantri, Riki; Syarif, Ahmad Fahrul Syarif; Valen, Fitri Sil (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
Bangka Island is one of Indonesia’s regions with significant potential in terms of freshwater fish diversity, particularly within the genus Betta, commonly known as wild bettas. This study aims to document species diversity, geographic distribution, and natural habitat characteristics of wild Betta populations on Bangka Island, which inhabit peat swamp ecosystems, blackwater rivers, and abandoned tin-mining ponds. Through field exploration and morphological identification, seven primary Betta species were recorded: Betta burdigala, B. schalleri, B. edithae, B. chloropharynx, B. uberis, B. cracens, and B. simorum. Each species occupies a distinct habitat type characterized by extreme water parameters, including low pH (4.2–5.8), minimal dissolved oxygen levels (0.8–2.5 mg/L), relatively stable water temperatures (26–30°C), and low conductivity. Certain species, such as B. burdigala and B. chloropharynx, exhibit unique physiological adaptations via the labyrinth organ, which enables aerial respiration. The species distribution is uneven across the island, with some species being restricted to specific localities, rendering them endemic. Major threats to these species include habitat degradation due to tin mining, oil palm plantation expansion, and environmental pollution. Recent data indicate that several populations are experiencing severe declines, with some nearing local extinction. Consequently, the findings of this study provide a critical foundation for ecosystem-based conservation strategies and the restoration of vital habitats. Scientifically, Bangka Island qualifies as a Betta biodiversity hotspot of strategic importance in the context of Southeast Asian biogeography and the conservation of endemic freshwater species.